The Effect of Outdoor Learning Methods to Improve Students' Understanding of Sciences at Elementary School - Tuga, Antonia Florensia C; Kua, Maria Yuliana; Suparmi, Ni Wayan; Laksana, Dek Ngurah Laba (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to determine the influence of out-of-class learning methods on improving students' understanding of science in SDK Majamere. This type of research is classroom action research (CAR), with the research method used being the Kemis and McTaggart model, which consists of planning, implementation, observation, and reflection. The approach used is quantitative and qualitative. The subjects in this study were 18 students of class V SDK Majamere. The research instruments used were observation sheets and learning outcome tests. This study showed a significant increase in students' understanding of science. The results of the percentage of student learning completeness increased from 33.3% in cycle I to 77.7% in cycle II. The results of observations of questioning activities increased from 27.7% in cycle I to 72.2% in cycle II. Answering activities increased from 16.6% in cycle I to 88.8% in cycle II. The activity of noting important material increased from 22.2% in cycle I to 55.5% in cycle II. Based on the results of this classroom action research, the impact of out-of-class learning methods can improve the understanding of science in grade V students at SDK Majamere.